Metatranscriptomic time series insight into antibiotic resistance genes and mobile genetic elements in wastewater systems under antibiotic selective pressure - An-Dong Li; Yuanfang Chen; Lei Han; Ye Li; Ming Xu; Baoli Zhu (BMC Microbiology)
Abstract Background Wastewater systems are usually considered antibiotic resistance hubs connecting human society and the natural environment. Antibiotic usage can increase the abundance of both ARGs (antibiotic resistance genes) and MGEs (mobile gene elements). Understanding the transcriptomic profiles of ARGs and MGEs remains a major research goal. Methods Batch experiments were conducted by adding ampicillin to fresh activated sludge to final concentrations of 100 and 20 mg/L. The ampicillin concentration was detected via UPLC‒MS/MS. Metatranscriptomic data from the samples in the reactors were detected in a time series (0 to 10 h). The transcription profiles of ARGs and MGEs were summarized by searching metatranscriptomic datasets against related databases. Results During incubation, the dosed ampicillin could be removed completely within 8.5 h and 4 h, following first-order biodegradation kinetics models (R 2 : 0.983–0.991). The phylogenetic composition and ARG profiles at the DNA level remained stable. At the transcriptional level, significant upregulation of a class A beta-lactamase (P14171 gene) was observed. The P14171 gene is mostly spread in wastewater treatment systems and is carried by Rhodobacteraceae. Transcription of MGEs (especially TnpA) and sul1 stimulated by external ampicillin. However, no significant correlations (ρ > 0.7, p < 0.01) between the ARGs and MGEs across all the metatranscriptomic datasets were detected. Conclusion The P14171 gene was the only key ARG that responded to ampicillin degradation in the tested activated sludge systems, indicating its ability and potential health risk. External ampicillin could accelerate HGT in activated sludge systems by increasing the transcription of MGEs.